Differences in trunk strength between weightlifters and wrestlers - Ben Moussa Zouita, A.; Zouita, S.; Dziri, C.; Brughelli, M.; Behm, D. G.; Chaouach, A. (Journal of Human Kinetics, 2019)
Investigations of trunk strength with high-level athletes are limited. The purpose of this study was to compare maximal concentric isokinetic trunk extension and flexion torque, power, and strength ratios between high-level weightlifters (n = 20), wrestlers (n = 20) and a control (n = 25) population. Isokinetic dynamometry was used to evaluate peak torque, power and strength ratios during seated trunk extension/flexion actions at 60°/s and 180°/s. There were no significant anthropometric differences between groups. Overall, trunk isokinetic force variables as a function of the increase in angular velocity, showed a decrease in peak torque, but an increase in power (athletes and controls). Compared to the control group, athletes demonstrated significantly higher trunk extension torque (+67.05 N·m, ES = 0.81) and power (+49.28 N·m, ES = 0.82) at 60°/s and 180°/s, respectively. Athletes produced significantly greater trunk flexion-extension ratios at 60°/s and 180°/s (ES = 0.80-0.47) than controls. Weightlifters and wrestlers exhibited significantly higher extensor than flexor torque at all angular velocities. Weightlifters demonstrated greater torque (ES = 0.79) than wrestlers at 60°/s. The wrestlers` average power was significantly higher (ES = 0.43) than weightlifters at 180°/s. There were no significant ratio differences between wrestlers (66.23%) and weightlifters (72.06%). Weightlifters had stronger extensor muscles at 60°/s, whereas wrestlers had higher power at 180°/s for extensor muscles. It was postulated that the extensor muscles were stronger than the flexors to ensure trunk stabilisation, and for prevention of injuries. These differences seem to be associated to the movements that occur in each sport in terms of both muscle actions and contractile forces. Keywords: isokinetic dynamometry; sport performance; spine; core; back